2019
DOI: 10.1186/s13059-019-1767-3
|View full text |Cite
|
Sign up to set email alerts
|

Linker histones are fine-scale chromatin architects modulating developmental decisions in Arabidopsis

Abstract: Background Chromatin provides a tunable platform for gene expression control. Besides the well-studied core nucleosome, H1 linker histones are abundant chromatin components with intrinsic potential to influence chromatin function. Well studied in animals, little is known about the evolution of H1 function in other eukaryotic lineages for instance plants. Notably, in the model plant Arabidopsis , while H1 is known to influence heterochromatin and DNA methylation, its cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
132
2
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(161 citation statements)
references
References 115 publications
(183 reference statements)
25
132
2
2
Order By: Relevance
“…These results suggest that reducing heterochromatin, rather than H3K9me2 marks associated with heterochromatin, is sufficient for siRNA production from long heterochromatic TEs. Accordingly, H1 promotes nucleosome occupancy on heterochromatic regions [62,63] , and we found that heterochromatic TEs were enriched for H1 ( Fig. 5g and Fig.…”
Section: Chromatin Regulates Small Rna Transcriptionmentioning
confidence: 64%
See 1 more Smart Citation
“…These results suggest that reducing heterochromatin, rather than H3K9me2 marks associated with heterochromatin, is sufficient for siRNA production from long heterochromatic TEs. Accordingly, H1 promotes nucleosome occupancy on heterochromatic regions [62,63] , and we found that heterochromatic TEs were enriched for H1 ( Fig. 5g and Fig.…”
Section: Chromatin Regulates Small Rna Transcriptionmentioning
confidence: 64%
“…Because linker histone 1 (H1) inhibits RNA polymerases binding to chromatin [58,59] , and its depletion results in the loss of chromocenters and chromatin compaction [60][61][62] , we tested whether decreased H1 levels during post-embryogenesis were sufficient to increase siRNA biogenesis throughout long heterochromatic TEs similar to what we observed in embryos. That is, we performed sRNA-seq on leaves carrying null mutations in the two expressed H1.1 and H1.2 isoforms (i.e.…”
Section: Chromatin Regulates Small Rna Transcriptionmentioning
confidence: 83%
“…1a) the linker histone contacts the nucleosome near the dyad 3 . Linker histones compact chromatin and H1 loss triggers precocious flowering in Arabidopsis 3, 69 . To probe for chromatin opening by LFY, we therefore next determined occupancy of the H1 linker histone in the absence and presence of LFY.…”
Section: Resultsmentioning
confidence: 99%
“…At a larger scale, loss of nuclear compartmentalization in the Arabidopsis 3h1 mutant lacking histone H1 correlates with a global diminution in H3K27me3 occupancy. This indicates that the 3D organization of chromatin into subnuclear domains probably contributes to the maintenance of H3K27me3 (Rutowicz et al, 2019), although its direct impact during replication needs to be clarified.…”
Section: The 3d Organization Of Chromatin Might Facilitate Local Retementioning
confidence: 99%